Safety and efficacy of adjunctive cenobamate (YKP3089) in patients with uncontrolled focal seizures: a multicentre, double-blind, randomised, placebo-controlled, dose-response trial. Issue 1 (January 2020) - Krauss, Gregory L; Klein, Pavel; Brandt, Christian; Lee, Sang Kun; Milanov, Ivan; Milovanovic, Maja; Steinhoff, Bernhard J; Kamin, Marc
Summary: Background: More than a third of patients with epilepsy are treatment resistant, and thus new, more effective therapies to achieve seizure freedom are needed. Cenobamate (YKP3089), an investigational antiepileptic drug, has shown broad-spectrum anticonvulsant activity in preclinical studies and seizure models. We aimed to evaluate the safety, efficacy, and tolerability of adjunctive cenobamate in patients with uncontrolled focal (partial)-onset epilepsy. Methods: We did a multicentre, double-blind, randomised, placebo-controlled, dose-response study at 107 epilepsy and neurology centres in 16 countries. Adult patients (aged 18–70 years) with focal seizures despite treatment with 1–3 antiepileptic drugs were randomly assigned (1:1:1:1) via an interactive web response system, by block sizes of 4 within each country, to adjuvant once daily oral cenobamate at dose groups of 100 mg, 200 mg, or 400 mg, or placebo following an 8-week baseline assessment. Patients, investigators, and study personnel were masked to treatment assignment. The study included a 6-week titration phase and 12-week maintenance phase. The primary efficacy outcomes were percentage change in 28-day focal seizure frequency (focal aware motor, focal impaired awareness, or focal to bilateral tonic-clonic seizures) from baseline analysed in the modified intention-to-treat population (≥1 dose and any post-baseline seizure data) and responder rates (≥50% reduction) analysed in the maintenance phase population (≥1 dose in the maintenance phase and any maintenance phase seizure data). The primary efficacy outcomes were analysed using a hierarchal step-down procedure comparing 200 mg versus placebo, 400 mg versus placebo, then 100 mg versus placebo. Safety and tolerability were compared descriptively across treatment groups for all randomised patients. This study is registered with ClinicalTrials.gov, number NCT01866111 . Findings: Between July 31, 2013, and June 22, 2015, 437 patients were randomly assigned to either placebo (n=108) or cenobamate 100 mg (n=108), 200 mg (n=110), or 400 mg (n=111). Of these patients, 434 (106 [98%] in placebo group, 108 [100%] in 100 mg group, 109 [99%] in 200 mg group, and 111 [100%] in 400 mg group) were included in the modified intention-to-treat population, and 397 (102 [94%] in placebo group, 102 [94%] in 100 mg group, 98 [89%] in 200 mg group, and 95 [86%] in 400 mg group) were included in the modified intention-to-treat maintenance phase population. Median percentage changes in seizure frequency were −24·0% (IQR −45·0 to −7·0%) for the placebo group compared with −35·5% (−62·5 to −15·0%; p=0·0071) for the 100 mg dose group, −55·0% (−73·0 to −23·0%; p<0·0001) for the 200 mg dose group, and −55·0% (−85·0 to −28·0%; p<0·0001) for the 400 mg dose group. Responder rates during the maintenance phase were 25% (26 of 102 patients) for the placebo group compared with 40% (41 of 102; odds ratio 1·97, 95% CI 1·08–3·56; p=0·0365) for the 100 mg dose group, 56% (55 of 98; 3·74, 2·06–6·80; p<0·0001) for the 200 mg dose group, and 64% (61 of 95; 5·24, 2·84–9·67; p<0·0001) for the 400 mg dose group. Treatment-emergent adverse events occurred in 76 (70%) of 108 patients in the placebo group, 70 (65%) of 108 in the 100 mg group, 84 (76%) of 110 in the 200 mg group, and 100 (90%) of 111 in the 400 mg group. Treatment-emergent adverse events led to discontinuation in five (5%) patients in the placebo group, 11 (10%) in the 100 mg dose group, 15 (14%) in the 200 mg dose group, and 22 (20%) in the 400 mg dose group. One serious case of drug reaction with eosinophilia and systemic symptoms occurred in the 200 mg cenobamate group. No deaths were reported. Interpretation: Adjunctive cenobamate reduced focal (partial)-onset seizure frequency, in a dose-related fashion. Treatment-emergent adverse events were most frequent in the highest dose group. Cenobamate appears to be an effective treatment option in patients with uncontrolled focal seizures. Funding: SK Life Science.